DETERMINANTS OF STUDENT ETHICAL BEHAVIOR: A STUDY ON ISLAMIC ACCOUNTING EDUCATION AND STUDENT RELIGIOSITY - Maulana, Fadhlan; Laela, Sugiyarti Fatma (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2024)
ABSTRACTThis study aims to analyze the impact of Islamic accounting education and the level of religiosity on ethical behavior. All variables were measured using a questionnaire instrument which was distributed to 53 undergraduate students majoring in Islamic accounting located in Java. The hypotheses were tested using multiple regression analysis. The results show that Islamic accounting education has a positive impact on ethical behavior represented in their daily life. However, the religiosity level does not affect ethical behavior. The implication of the study is the importance of integrating religious values into learning. The values of Islam are universal, such as honesty, trustworthiness, and professionalism, and can be applied to individuals from any religious background. In addition, these values must be internalized. As a result, religion is not just ritual worship, but also has an impact on social piety.ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh pendidikan akuntansi Islam dan tingkat religiusitas terhadap perilaku etis. Seluruh variabel diukur menggunakan instrumen kuesioner yang dibagikan kepada 53 mahasiswa S1 jurusan akuntansi syariah yang berlokasi di Pulau Jawa. Hipotesis diuji dengan menggunakan analisis regresi berganda. Hasil penelitian menunjukkan bahwa pendidikan akuntansi Islam mempunyai dampak positif terhadap perilaku etis responden yang direpresentasikan dalam kehidupan sehari-hari. Namun tingkat religiusitas tidak mempengaruhi perilaku etis. Implikasi dari penelitian ini adalah pentingnya mengintegrasikan nilai-nilai agama ke dalam pembelajaran. Nilai-nilai Islam bersifat universal, seperti kejujuran, amanah, profesionalisme dapat diterapkan pada individu dari latar belakang agama apa pun. Selain itu, nilai-nilai tersebut harus diinternalisasikan sehingga, agama bukan sekadar ibadah ritual, namun juga berdampak pada kesalehan sosial.